STUDI EMPIRIS TENTANG EFEKTIVITAS PERLINDUNGAN HUKUM TERHADAP PEMBELI DALAM JUAL BELI TANAH SENGKETADI KUPANG(Studi Kasus Tanah Di Naimata) - Firgilius Kandro Mego Asman; Giovani Don Bosco Nggabut; Bendiktus Peter Lay (JOURNAL OF LAW AND NATION, 2023)
Average selling rights to land according to Regulation No. 24 of 1997 shall be evidenced by a deed made by a PPAT. Changes in this procedure does not negate the provisions of customary law governing the institution in terms of material and selling land rights. But people still buy and sell land rights under hand. One example of the results of the study authors found cases of buying and selling land rights conducted under the hand of the study sites namely residential areas in the village area Madyopuro Kedungkandang subdistrict, Malang. Sale and purchase of land rights are carried out under the hand has problems, especially for buyers who will make the process to change the name of the certificate to be registered to the Land Office of Malang. Therefore, if the sale and purchase of land rights is conducted under the hand, it can not be registered at the Land Office of Malang to be processed to change the name in the certificate Research conducted in this thesis is an empirical study using sociological juridical approach. Based on these results above regarding legal protection for the buyer to do a sale and purchase of land rights under hand it can be concluded (1) the buyer does not get the legal protection of land he had bought; (2) the buyer does not obtain legal certainty on the land he had bought; (3) the buyer does not get strong evidence right on land bought. This of course would be detrimental to the buyer who purchases land rights committed under hand. This event is expected to bring to the community, especially for the buyers when buying and selling land rights should be conducted in the presence of PPAT so get protection and legal certainty of land bought.